PELAKSANAAN PATROLI SAMPAH OLEH PRAMUKA SEBAGAI PENINGKATAN KEPEDULIAN LINGKUNGAN KAMPUS UNIKA St THOMAS MEDAN - Heka Maya Sari Br Sembiring; Rizki Bastanta Manalu; Wenny Simanjorang; Sumber Napitupulu; Haldi Anni Tungkir; Okta Elsa Br Sidabariba (ASOSIASI IDEBAHASA KEPRI, 2026)
The Waste Patrol Program at Santo Thomas Catholic University Medan, organized by the Scout Movement, is a community service initiative based on Community-Based Service Learning (CBSL). It aims to raise environmental awareness and promote sustainable behavior among the academic community. The program was created to address poor campus waste management and low student concern for cleanliness. Through participatory and educational methods, Scout students act as change agents by conducting cleanliness patrols, sorting organic and inorganic waste, and teaching environmental responsibility using the 3R principles (Reduce, Reuse, Recycle). Implementation follows three stages: preparation, execution, and evaluation/reflection, supported by observation, documentation, and simple data analysis. Results show notable progress: campus waste volume decreased by over 20%, while student participation in cleanliness activities rose by more than 50%. The program also fostered a culture of environmental awareness, reflected in regular waste segregation, material reuse, and independent initiatives to maintain campus hygiene. In conclusion, the Waste Patrol Program effectively shapes environmentally literate student character and contributes to building a clean, healthy, and sustainable green campus.